Sexual imagery in advertising: issues in consumer motivational processes - Pagiaslis, Anastasios (2015)
Grounded in Self Determination Theory (Deci and Ryan 1985a; 2000), the purpose of this thesis is to investigate the unintentional and pernicious effects of sexual imagery in advertising on life aspirations, situational motivation for consumption, satisfaction with basic needs, state self-esteem and body image (dis)satisfaction while accounting for the mediating effects of the individual differences variables: contingent self-esteem, general causality orientations and sexual liberalism. Results from two laboratory experiments test the hypotheses. Data were collected via a series of quasi-experiments utilizing a 2 x 4 full factorial design; gender served as a 2-level quasi-experimental variable and nudity as a 3-level experimental variable (nude, semi-nude, clothed) with a product-only condition as the control condition. The experimental stimuli comprised 16 advertisements utilizing products relevant to sexual imagery (Vodka, Whiskey, Wrist watches, Jeans and Perfumes). Before exposure to the experimental stimuli, participants were asked to complete the individual differences questionnaires, and after exposure to the experimental stimuli, participants were asked to complete the questionnaire comprising the outcome variables and basic demographic information. The results provide counter-intuitive information about the function of sexual imagery across increasing levels of nudity and across genders. The original hypotheses about the directionality of effects hold only partially. Individuals exhibit mixed results regarding the effects in aspirations (study 1 and study 2), the situational motivation for consumption is not found to differ across conditions (study 1 and 2), state self-esteem and body image (dis)satisfaction show indications compensatory mechanisms but only for study 1. In study 2 sexual imagery impacts the satisfaction with basic needs. Females are more pre-occupied with image, meaningful relationships and health (study 1 and study 2) while men are more preoccupied with fame (study 1). Females also exhibit lower state self-esteem (study 1) and lower body satisfaction (study 1). Taken together the results indicate that the negative effects of sexual imagery can be offset by conscious image processing, autonomous self-determination and other defensive strategies. Finally, differences between advertising conditions of nudity may be susceptible to arousal and mating profile effects.